Natural History and Ecology of Mexico and Central America 2021
DOI: 10.5772/intechopen.96655
|View full text |Cite
|
Sign up to set email alerts
|

Rediscovering Kemp’s Ridley Sea Turtle (Lepidochelys kempii): Molecular Analysis and Threats

Abstract: Sea turtles are reptiles that have inhabited the earth for 100 million years. These are divided into 2 families (Cheloniidae and Dermochelyidae) and 7 species of sea turtles in the world: the leatherback turtle (Dermochelys coriacea); hawksbill turtle (Eretmochelys imbricata); Kemp’s ridley (Lepidochelys kempii); olive ridley (L. olivacea); Loggerhead turtle (Caretta caretta); flatback sea turtle (Natator depressus) and green turtle (Chelonia mydas). In particular, Kemp’s ridley is included in the red list of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Similar trends in Kemp's ridley nesting have been documented. After decades of apparent recovery, Kemp's ridley nesting declined significantly in 2010 and full recovery from that decline remains unclear as do the reasons for the declines (Galloway et al, 2016 ; Reyes‐López et al, 2021 ). Tagging studies in the northern Gulf of Mexico showed that these loggerheads exhibited extremely low nesting site fidelity (Hart et al, 2014 ; Lamont et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar trends in Kemp's ridley nesting have been documented. After decades of apparent recovery, Kemp's ridley nesting declined significantly in 2010 and full recovery from that decline remains unclear as do the reasons for the declines (Galloway et al, 2016 ; Reyes‐López et al, 2021 ). Tagging studies in the northern Gulf of Mexico showed that these loggerheads exhibited extremely low nesting site fidelity (Hart et al, 2014 ; Lamont et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…By the mid‐1980s, nest numbers had declined to 700–800 deposited annually (Reyes‐López et al, 2021) and the population was estimated at approximately 300 nesting females (National Marine Fisheries Service, US Fish and Wildlife Service & SEMARNAT, 2011; Bevan et al, 2016). These declines have been attributed primarily to the mortality of Kemp’s ridleys in commercial fisheries and poaching of eggs for human consumption (National Marine Fisheries Service, US Fish and Wildlife Service & SEMARNAT, 2011; Reyes‐López et al, 2021). A bi‐national effort between the US and Mexico (Marquez, 1989), which included establishment of a secondary nesting population at Padre Island National Seashore in southern Texas and required the use of Turtle Excluder Devices on US fishing boats (National Marine Fisheries Service, US Fish and Wildlife Service & SEMARNAT, 2011), is credited with leading the Kemp’s ridley back towards recovery.…”
Section: Introductionmentioning
confidence: 99%
“…In 1947, more than 40,000 nests were documented in one day on the main nesting beach in Rancho Nuevo, Mexico, and it has been estimated that the population at that time consisted of more than 48,000 nesting females (Bevan et al, 2016). By the mid‐1980s, nest numbers had declined to 700–800 deposited annually (Reyes‐López et al, 2021) and the population was estimated at approximately 300 nesting females (National Marine Fisheries Service, US Fish and Wildlife Service & SEMARNAT, 2011; Bevan et al, 2016). These declines have been attributed primarily to the mortality of Kemp’s ridleys in commercial fisheries and poaching of eggs for human consumption (National Marine Fisheries Service, US Fish and Wildlife Service & SEMARNAT, 2011; Reyes‐López et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations